2011
DOI: 10.1016/j.neuroscience.2011.05.020
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β signaling is required for maintenance of retinal ganglion cell differentiation and survival

Abstract: Purpose To determine the role of TGF-β1 in the maintenance of retinal ganglion cell line (RGC-5) differentiation and integrity. Methods RGC-5 cells were differentiated in media conditioned by human non-pigmented ciliary epithelial cells (HNPE) for four days before treatment with TGF-β1 for 24 hr. Cells were examined for morphological changes and harvested for western blot and real-time PCR analysis. For study of apoptosis, differentiated RGC-5 cells were grown in serum-free medium for 24 hr in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…TGF-β1 knock-out mice show prominent neuronal cell death in various parts of the brain (Brionne et al, 2003), and genetic reduction of TGF-β2 leads to a loss of dopaminergic neurons in mice (Andrews et al, 2006). Cell culture studies have also shown that TGF-β signaling is required for maintaining neuronal survival after various insults (Bruno et al, 1998;Walshe et al, 2011;Zhu et al, 2002). Inhibition of TGF-β signaling specifically in neurons leads to increased neurodegeneration (Tesseur et al, 2006).…”
Section: Smad3 Signaling Involved In Neuroprotection May Be Initiatedmentioning
confidence: 99%
“…TGF-β1 knock-out mice show prominent neuronal cell death in various parts of the brain (Brionne et al, 2003), and genetic reduction of TGF-β2 leads to a loss of dopaminergic neurons in mice (Andrews et al, 2006). Cell culture studies have also shown that TGF-β signaling is required for maintaining neuronal survival after various insults (Bruno et al, 1998;Walshe et al, 2011;Zhu et al, 2002). Inhibition of TGF-β signaling specifically in neurons leads to increased neurodegeneration (Tesseur et al, 2006).…”
Section: Smad3 Signaling Involved In Neuroprotection May Be Initiatedmentioning
confidence: 99%
“…In cultured cortical neurons, TGF-b-induced inhibition of axonal growth was eliminated by SB431542 treatment or Smad2 knock-down (Stegmüller et al, 2008;Ylera et al, 2009). However, in RGC-5 cells transformed form retinal ganglion cells TGF-b promoted neurite growth through a noncanonical TGF-b/Smad signaling pathway (Walshe et al, 2011). In our study, TGF-bs exhibited an inhibitory effect on neurite growth and blocking TGF-b/Smad signaling with the TbRI inhibitor SB431542 or Smad2 shRNA also increased neurite growth, which support a role for TGF-b signaling in the negative regulation of growth in DRG neurons.…”
Section: The Tgf-b/smad Signaling Pathway Mediates the Ipp5-induced Imentioning
confidence: 99%
“…10 Similarly, experimental systemic inhibition of TGF-β1 and TGF-β3, achieved by overexpression of sEng, leads to vascular permeability and perfusion defects as well as apoptosis of both vascular and non-vascular tissues. 11 sEng overexpressing mice also demonstrate an essential role for TGF-β in maintaining the endothelium in a non-activated state 12 and in maintaining microvessel integrity and function in the retina and choroid plexus. 13,14 Previous reports demonstrate that TGF-β signaling between EC and mural cells participates in vessel stabilization in vivo and in vitro, and paracrine TGF-β signaling between ECs and surrounding mural cells and astrocytes is well documented.…”
Section: Introductionmentioning
confidence: 98%
“…13,14 Previous reports demonstrate that TGF-β signaling between EC and mural cells participates in vessel stabilization in vivo and in vitro, and paracrine TGF-β signaling between ECs and surrounding mural cells and astrocytes is well documented. 11,1517 …”
Section: Introductionmentioning
confidence: 99%